Environmental contaminants assessment and control - Vallero, Daniel A. (Amsterdam ; Boston : Elsevier Academic Press, 2004)
This book serves as a tool for environmental professionals to produce technically sound and reproducible scientific evidence. It identifies ways to clean up environmental problems in air, water, soil, sediment and living systems. Ethical issues, environmental management, and professionalism, and environmental economic problems are illustrated to assist the reader in understanding and applying quantitative analysis of environmental problems. Companion Website http://books.elsevier.com/companions/0127100571 *Real life solutions for practicing environmental professionals. *Example problems, sidebars, and case studies to illustrate ethical issues, environmental economic problems, and environmental management. *Explanation of scientific principles and concepts needed for risk assessment, waste management, contaminant transport, environmental hydrogeology, and environmental engineering & chemistry. *A fully supportive glossary, appendices and tables throughout the text contain physical, chemical and biological resources necessary for all environmental practitioners.
Part I: An Environmental Policy Primer: -- 1. Scientific and Engineering Perspectives of Environmental Contaminants -- Part II: Fundamentals of Environmental Science and Engineering -- 2. Fundamentals of Environmental Physics -- 3. Applied Contaminant Physics: Fluid Properties -- 4. Environmental Equilibrium, Partitioning, and Balances -- 5. Movement of Contaminants in the Environment -- 6. Fundamentals of Environmental Chemistry -- 7. Chemical Reactions in the Environment -- 8. Biological Principles of Environmental Contamination -- Part III: Contaminant Risk -- 9. Contaminant Hazards -- 10. Contaminant Exposure and Risk Calculations -- Part IV: Interventions to Address Environmental Contamination -- 11. Contaminant Sampling and Analysis -- 12. Intervention: Managing the Risks of Environmental Contamination -- 13. Environmental Decisions and Professionalism -- 14. Epilogue: Benzene Metabolism Revisited -- Glossary of Environmental Sciences and Engineering Terminology; Appendices; Index.
Includes bibliographical references and index.
Keywords: Environmental risk assessment; Environmental protection; Polluants; Environnement -- Surveillance; Electronic books